From Initiators to Effectors: Roadmap Through the Intestine During Encounter of Toxoplasma gondii With the Mucosal Immune System - Snyder, Lindsay M.; Denkers, Eric Y. (Frontiers in Cellular and Infection Microbiology, 2021)
The gastrointestinal tract is a major portal of entry for many pathogens, including the protozoan parasite Toxoplasma gondii. Billions of people worldwide have acquired T. gondii at some point in their life, and for the vast majority this has led to latent infection in the central nervous system. The first line of host defense against Toxoplasma is located within the intestinal mucosa. Appropriate coordination of responses by the intestinal epithelium, intraepithelial lymphocytes, and lamina propria cells results in an inflammatory response that controls acute infection. Under some conditions, infection elicits bacterial dysbiosis and immune-mediated tissue damage in the intestine. Here, we discuss the complex interactions between the microbiota, the epithelium, as well as innate and adaptive immune cells in the intestinal mucosa that induce protective immunity, and that sometimes switch to inflammatory pathology as T. gondii encounters tissues of the gut.